Mitochondria-Targeting and ROS-Responsive Nanocarriers via Amphiphilic TPP-PEG-TK-Ce6 for Nanoenabled Photodynamic Therapy - Yangjian Wang; Junshui Zheng; Jian Lin; Kai Ye; Peng Wei (Advances in Polymer Technology)
Designing targeted-delivering and stimuli-responsive nanocarriers for photodynamic therapy (PDT) is an appealing method, especially, targeting delivery of photosensitizers to mitochondria as the most sensitive cellular organelles to reactive oxygen species (ROS) could significantly enhance the therapeutic efficacy of PDT. In this study, we synthesized triphenylphosphonium bonded PEG-NH2 (TPP-PEG-NH2) and bridged to chlorin e6 (Ce6) via thioketal (TK) linkage to obtain red light-triggered, amphiphilic copolymer (TPP-PEG-TK-Ce6), which could self-assemble into micelles with an average size of 160 nm and zeta potential of +20.1 mV. The in vitro release behavior of TPP-PEG-TK-Ce6 nanocarriers showed a light-activated way and was dependent on the H2O2 concentration. TPP-PEG-TK-Ce6 nanocarriers exhibited high cytotoxicity against C6 cells with illumination. Confocal laser scanning microscopy observation indicated that TPP-PEG-TK-Ce6 nanocarriers were efficiently internalized into the mitochondrion of C6 cells, released Ce6 via light activated. By contrast, in the case of TPP-PEG-NH2 directly bonded Ce6 (TPP-PEG-Ce6) nanocarriers, little Ce6 was found in the mitochondrion. The stronger fluorescence in the mitochondrion of TPP-PEG-TK-Ce6 nanocarriers originated from the mitochondrial-targeting capability of TPP and the cleavage of TK linkages activated by light irradiation, which greatly improved the cellular uptake of TPP-PEG-TK-Ce6 nanocarriers and released more Ce6 in the mitochondrion. This work provided a facile strategy to improve PDT efficacy.